Influence of fatty acids composition in different tissue of mice feeds with fish oils (Research, Society and Development, 2021)
Omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) play an important role in human health. Fish oils enriched with EPA and DHA have commercialized in triacylglycerol (TAG) and ethyl ester forms (EE). In this study, we compared the impact of diets containing fish oil in ethyl ester and triacylglycerol forms as a lipid source in five different tissues as liver, skeleteral muscle, brain, and epididymal white adipose tissue (WAT). The DHA levels were higher in the WAT and skeletal muscle of TAG and EE groups in comparison with the SB group. The body weight and brain, liver, epididymal WAT, and gastrocnemius muscle weights, and serum glucose, TG, cholesterol were not different between the groups. Thus, we conclude that EPA and DHA in the form of EE or TAG influence the fatty acids composition of different tissues.